# Second Shifting Property of Laplace Transforms: Formula, Proof

The second shifting property of Laplace transforms is used to find the Laplace of a function multiplied by a unit step function. Let us discuss the second shifting property, its proof and some solved examples.

Before we proceed, let us recall the definition of a unit step function. It is defined as follows:

u(t-a) = $\begin{cases} 1 & \text{ if } t>a \\ 0 & \text{ if } t < a \end{cases}$

## Second Shifting Property Statement

Let L{f(t)} = F(s). For a>0 we have

As L{f(t)} = F(s), by definition of Laplace transforms we have that

F(s) = $\int_0^\infty$ e-st f(t) dt.

Now, L{f(t-a) u(t-a)}

= $\int_0^\infty$ e-st f(t-a) u(t-a) dt

= $\int_a^\infty$ e-st f(t-a) dt, by the definition of unit step function.

We now make a change of variable. Let us put

z=t-a.

So dz=dt.

Therefore, from above we obtain that

L{f(t-a) u(t-a)} = $\int_0^\infty$ e-s(z+a) f(z) dz

= e-as $\int_0^\infty$ e-sz f(z) dz

= e-as F(s).

This proves the second shifting property of Laplace transforms whose formula states that L{f(t-a) u(t-a)} = e-as F(s) for a>0.

Laplace Transform: Definition, Table, Formulas, Properties

## Solved Examples

Question: Find the Laplace of (t-2) u(t-2), that is, find L{(t-2) u(t-2)}.

Put a=2 in the second shifting property. Thus,

L{(t-2) u(t-2)} = e-2s F(s)

where F(s)= L{t} = 1/s2.

So, L{(t-2) u(t-2)} = $\dfrac{e^{-2s}}{s^2}$

So the Laplace of (t-2) u(t-2) is equal to e-2s/s2.

## FAQs

Q1: What is the second shifting property of Laplace transforms?

Answer: The second shifting property of Laplace transforms states that if L{f(t)} = F(s) then L{f(t-a) u(t-a)} = e-as F(s) for a>0. Here u(t-a) is the unit step function.

Share via: